2004
DOI: 10.1128/jb.186.15.5040-5051.2004
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Whole-Genome Hybridization Reveals Genomic Islands inBrucellaSpecies

Abstract: Brucella species are responsible for brucellosis, a worldwide zoonotic disease causing abortion in domestic animals and Malta fever in humans. Based on host preference, the genus is divided into six species. Brucella abortus, B. melitensis, and B. suis are pathogenic to humans, whereas B. ovis and B. neotomae are nonpathogenic to humans and B. canis human infections are rare. Limited genome diversity exists among Brucella species. Comparison of Brucella species whole genomes is, therefore, likely to identify f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
96
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(101 citation statements)
references
References 52 publications
5
96
0
Order By: Relevance
“…This might suggest that the island cannot be spontaneously separated from the genome. GI-3 is flanked by direct repeats of 18 bp (27), and the low number of base pairs might explain the low mobility of this genetic element in wild strains, despite the fact that this island displayed characteristics typical of GIs (12). The stability of GI-3 confirms, as reported by other authors, that the genomes of Brucella species are very stable and similar (37).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…This might suggest that the island cannot be spontaneously separated from the genome. GI-3 is flanked by direct repeats of 18 bp (27), and the low number of base pairs might explain the low mobility of this genetic element in wild strains, despite the fact that this island displayed characteristics typical of GIs (12). The stability of GI-3 confirms, as reported by other authors, that the genomes of Brucella species are very stable and similar (37).…”
Section: Discussionsupporting
confidence: 72%
“…These islands can encode metabolic pathways and/or virulence factors, providing new features that can transform a nonpathogenic bacterium into a pathogenic bacterium (12). Nine GIs have been identified in B. melitensis, and two of them (GI-4 and GI-8) are missing in B. abortus (27). Subsequent studies reported that of these nine islands present in Brucella, GI-1, GI-5, and GI-6 do not contribute to Brucella virulence (26).…”
mentioning
confidence: 99%
“…Furthermore, they showed that BMEI0999, a hypothetical protein whose function is unknown, was necessary to restore a smooth LPS in rough strains. However, we have found that other (46,60). The B. ovis genome also has a truncated wzt; this gene encodes a protein that functions as a part of an ABC transporter, with its partner encoded by wzm.…”
Section: Discussionmentioning
confidence: 99%
“…We used the following species-or strain-specific genetic differences to design PCR primers: (a) a 25-kb DNA deletion leading to the loss of omp31 gene in the reference strains of all B. abortus biovars (6, 7 ); (b) a 15-kb deletion comprising omp25b and wboAwboB genes in the Brucella ovis species (6, 7 ); (c) a wboA gene disruption by an IS711 element in the B. abortus vaccine strain RB51 (8 ); (d) a 702-bp deletion in the ery operon in the vaccine strain B. abortus S19 (9 ); (e) a specific mutation in the rpsL gene of the vaccine strain B. melitensis Rev1 that differentiates it from the B. melitensis reference strain (10 ); (f) a 976-bp deletion in chromosome I specific to Brucella canis (7 ); (g) a 2.2-kb deletion in chromosome II specific to Brucella neotomae (7 ); (h) a 2.6-kb fragment in B. suis, but not in B. abortus or B. melitensis (6,7 ); and (i) an IS711 element downstream of the bp26 gene in Brucella spp. isolated from marine mammals (11 ).…”
mentioning
confidence: 99%